136 What actually happens in a specialist heart failure clinic?. (4th June 2021) - Singhal, Arvind; Pan, Jiliu; Cassimon, Barbara; Cowie, Martin
Abstract : Introduction: Provision of specialist outpatient services has struggled to keep up with the growing demands of the heart failure (HF) epidemic in the UK. The Covid-19 pandemic necessitated a dramatic change in how HF clinics are delivered, with a reduction in face-to-face contact. The need for in-person appointments remains unknown. We evaluated pre-pandemic face-to-face clinic appointments in detail, to see what appointments achieved, in order to plan future services. Methods: We conducted a retrospective cohort study of patients who had completed 3 years of follow up (1st January 2017 to 31st December 2019) in a specialist HF clinic. Inclusion criteria were a clinician diagnosis of HF or left ventricular systolic dysfunction (from clinic letters and echocardiography), or at least moderate valvular disease with symptoms. Patient electronic health records were reviewed, and for each clinic attendance, the following were noted:Presence of new or worsening symptoms or signs of HF, or symptoms relating to HF treatment, as assessed by the clinicianChange in cardiovascular medicationsInvestigations requestedDocumented patient education, advice, or discussion of care plan Results: 100 patients were included in the cohort. The median age was 68, and patients were predominantly male (80%) with HFrEF (78%). There was a total of 666 appointments over the 3 years of follow up. Patients had a median of 2 appointments per year ( Figure 1 ). Figure 2 shows the frequency of investigations, symptoms and clinician actions in appointments. 21% of appointments documented new or worsening HF or treatment-related symptoms, and cardiovascular therapy was changed in 36% of appointments, ranging from 55% of nurse-led appointments to 31% where the patient saw a junior doctor. Therapy change was more common in appointments when there was a change in symptoms (53% vs 31%, p <0.001). 41% of patients had no documented worsening in HF symptoms throughout the entire 3 year follow up period. Patient education or clinical advice was documented in 32% of appointments. Follow-up duration was shorter following a change in symptoms (127 vs 163 days, p=0.03) and therapy change (128 vs 170 days, p=0.03). 45% of appointments had no documented worsening HF symptoms, change in cardiovascular therapy, specialist referral or specialist test (excluding echocardiography and phlebotomy); we consider these to be 'routine' follow-up appointments. Conclusion: Most HF patients were seen in a specialist HF clinic at least 6-monthly, but worsening symptoms and therapy change at the time of consultation were uncommon. Investigations other than phlebotomy and echocardiography, which may be performed outside of specialist centres, were rarely performed. Many appointments may therefore be suitable for community services or by telemedicine, thus freeing up capacity and responsiveness of in-person specialist clinics for patients with more complex needs, worsening symptoms or new diagnoses. Conflict of Interest: Dr Singhal's salary is funded by a fellowship from Abbott